2017
DOI: 10.1038/emi.2017.34
|View full text |Cite
|
Sign up to set email alerts
|

Identification and evaluation of the novel immunodominant antigen Rv2351c from Mycobacterium tuberculosis

Abstract: There is an urgent need for new immunodominant antigens to improve the diagnosis of tuberculosis (TB) and the efficacy of the TB vaccine to control the disease worldwide. In this study, we evaluated the diagnostic potential of a novel Mycobacterium tuberculosis (MTB)-specific antigen, Rv2351c, from region of difference (RD) 7 of the MTB genome, and investigated the potency of the vaccine by identifying its immunological function in human and animal immunological experiments. Twenty T-cell epitopes were identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 43 publications
(40 reference statements)
0
7
0
Order By: Relevance
“…116 The combination of TB with HIV/AIDS and the development of multidrug-resistant strains have increased the disease burden. 117 Immunotherapy might present a new option for treating drug-resistant TB strains, with promising outcomes and better quality of life for patients.- 118 Intramuscular immunization of Lohmann laying hens showed an increase of anti-MTBC IgY antibodies in egg yolk, with peak concentration at 4 weeks after immunization. The specific antibodies were persist 200 days after the last immunization.…”
Section: Mycobacterium Tuberculosismentioning
confidence: 99%
“…116 The combination of TB with HIV/AIDS and the development of multidrug-resistant strains have increased the disease burden. 117 Immunotherapy might present a new option for treating drug-resistant TB strains, with promising outcomes and better quality of life for patients.- 118 Intramuscular immunization of Lohmann laying hens showed an increase of anti-MTBC IgY antibodies in egg yolk, with peak concentration at 4 weeks after immunization. The specific antibodies were persist 200 days after the last immunization.…”
Section: Mycobacterium Tuberculosismentioning
confidence: 99%
“…Previously, we have evaluated the immunogenicity of several antigens from MTB, both in full-length and truncated modalities (T cell epitope focused regions). The results suggested that the antigens possessed high immunogenicity and may have promising effects on TB vaccine development [ 13 , 14 , 15 ]. On the basis of these efforts, we designed two multistage antigen complexes Epera013f and Epera013m, which comprised three full-length antigens EsxH, EsxB and Ag85B and two truncated antigens new RipD (nRipD) and new PPE18 (nPPE18), either as a protein mixture (Epera013m) or a fusion protein (Epera013f).…”
Section: Introductionmentioning
confidence: 99%
“…The frequently used T-cell epitope prediction tools include TEpredict, which is based on the data of HLA allele genotypic frequencies and the online tools of IEDB-AR database (Immune Epitope Database and Analysis Resource). Work by Wang X et al [ 14 ] suggested that a combined utilization of two T-cell epitope prediction tools might improve the accuracy and efficiency of the predicted epitopes and facilitate the advance of vaccine development.…”
Section: Introductionmentioning
confidence: 99%
“…Indonesia has the second largest burden of TB cases in the world after India. In 2017, there were 425,089 TB cases in Indonesia, indicating a dramatic increase compared to the previous year of 360,565 cases with a mortality rate of 42 per 100,000 population (Wang et al, 2017; WHO 2018; Ministry of Indonesia Health 2018). The problem of preventing and controlling TB is very complex because the effective TB treatment and accurate diagnosis are not established yet (Guginno et al, 2015).…”
Section: Introductionmentioning
confidence: 99%